Analisis Faktor Penerimaan TikTok Go sebagai Layanan E-voucher Berbasis Modifikasi UTAUT2 dengan Metode PLS-SEM - Amira Aurelia Salsabila; Daniel Arsa; Miranty Yudistira (CV. Graha Mitra Edukasi, 2026)
TikTok, as the fastest-growing social media platform in Indonesia, launched the TikTok Go service in February 2025. However, despite TikTok's massive user base in Indonesia, the market penetration of TikTok Go remains very low, at approximately 0.4% compared to 20% in the Chinese market. This low adoption rate potentially hinders service development, reduces platform revenue potential, limits incentives for content creators, and threatens the sustainability of partnerships with merchants. This phenomenon is supported by user review findings regarding various operational issues, such as technical glitches where barcodes fail to appear, data inconsistencies in product availability between merchants and the platform, and limited purchasing features in certain locations. This study aims to analyze the factors influencing user acceptance of TikTok Go by integrating a modified UTAUT 2 model. Data were collected through questionnaires from 180 respondents in Indonesia who have made at least two e-voucher purchases. The analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the structural and measurement models. The results indicate that Facilitating Conditions and Price Value significantly influence Purchase Intention. Furthermore, Habit and Purchase Intention significantly affect Use Behavior, while Social Commerce Construct plays a crucial role in enhancing User Trust. These findings confirm that strengthening facility support, optimizing pricing strategies, and fostering user habits are key drivers for increasing service adoption. Consequently, this study provides strategic recommendations for platform management to optimize facility support, pricing strategies, and engagement programs to enhance TikTok Go service adoption in Indonesia.